CHARACTERISATION OF UK ANTI-HMGCR+ ANTIBODY ASSOCIATED MYOSITIS. Issue 12 (15th November 2016) - Murphy, Sean; Lilleker, James; Rothwell, Simon; Betteridge, Zoe; McHugh, Neil; Roberts, Mark; Lamb, Janine; Cooper, Robert; Chinoy, Hector
Abstract : Introduction: Anti-HMG-CoA Reductase (anti-HMGCR) antibodies are associated with an immune-mediated necrotising myopathy related to previous 'statin' use. The role of this antibody in pathogenesis is incompletely understood. We have thoroughly characterised a cohort of anti-HMGCR associated myositis patients to increase understanding of the role of this antibody. Methods: We identified patients, as part of the UKMYONET cross-sectional myositis study, with anti-HMGCR antibodies and obtained further clinical, serotypic (Immunoprecipitation and ELISA) and genetic data (HLA Imputation using SNP2HLA) for analysis. Results: Anti-HMGCR antibodies were observed in 2.7% (37/1379 patients) of the UKMYONET database. The predominant reported clinical diagnoses in these patients were polymyositis (21/37) and statin associated myositis (7/37). A positive anti-HMGCR antibody was associated with: HLA-DRB1*11 (53.8% vs 9.9% in anti-HMGCR negative patients, p=0.01), previous statin exposure (31.4% vs 28.6% p=0.032), and higher median peak-creatine kinase (6945.5U/L vs 1159.0U/L, p=0.001). The frequency of anti-HMGCR antibody positivity in the UK appears lower than that seen in other international cohorts (although this may be dependent on the type of patients targeted for collection). Conclusion: The relationship between anti-HMGCR positivity, HLA-DRB1*11 and statin exposure confirms observations made in other international cohorts. Work is on going to characterise symptomatology, disease association and treatment response.